RDC 7: Conhecimento do enfermeiro de unidade de terapia intensiva - Vaz, Edson Muzi; Oliveira, Fernanda de Souza Cunha; Visentin, Angelita; Montezeli, Juliana Helena; Hey, Ana Paula; Brey, Christiane; Caveião, Cristiano (Cadernos da Escola de Saúde, 2017)